Understanding fan pressures and its impact on football club sustainability: insights from the Colombian context - Hernández-Hernández, Juan Alejandro; Londoño-Pineda, Abraham; Cano, Jose Alejandro (Frontiers in Sports and Active Living, 2024)
The framework of stakeholder pressures in sports industries, and in the specific case of football, has been used to identify the reasons why management bodies incorporate interested parties into their business strategy. This is primarily contingent on the pressures that interested parties generate. One of the most influential stakeholders is the fan base, given the emotional attachment that this type of sport evokes in them, commonly referred to as “the fan's affective connection.” Despite the existence of studies on diverse typologies of fans, no investigation has been conducted into the impact these have on the sustainability outcomes of football clubs. Moreover, most existing studies have focused on European leagues, with a pronounced emphasis on the environmental dimension of sustainability. Therefore, the aim of this research is to evaluate the impact of diverse fan types on the sustainability performance of Colombian football clubs, with a specific focus on the triple bottom line approach. To this end, two major fan typologies—active and non-active—were defined based on the findings of the literature review, as well as the pressures associated with solidarity-based factors. A conceptual model and an estimation based on the structural equation model related the different fan typologies and their associated pressures to sustainability outcomes. The results indicate that among the solidarity-based pressures, fans valued social commitment the most, followed by the promotion of women's football and the fight against racism. Environmental engagement was the least relevant, but still positively rated, suggesting the need for awareness-raising efforts to extend fans' sustainability practices beyond the stadium. The findings of this research can inform strategies for football clubs to engage fans and improve their sustainability performance across economic, social and environmental dimensions.